The Influence of Seasonal Price Discounts on Online Impulsive Buying Decisions on the Steam Gaming Platform (Study on Generation Z in Bandung) - Muhammad Ghazi Raiqal; Mukaram Mukaram (Dinasti Review, 2025)
The rapid growth of the digital gaming industry has intensified the use of seasonal price discounts as a marketing strategy to boost consumer purchasing interest. This study aims to examine the influence of seasonal discounts on impulsive buying decisions among Generation Z users in Bandung, Indonesia, on the Steam platform. A quantitative approach with a survey method was adopted, involving 111 respondents selected through purposive sampling. The collected data were analyzed using simple linear regression. The results reveal a significant and positive influence of seasonal discounts on impulsive buying behavior, with a correlation coefficient (r) of 0.744 and a coefficient of determination (R²) of 55.4%. These findings suggest that seasonal discounts substantially drive impulsive purchase behavior among Gen Z users on Steam. The study offers practical insights for digital marketing practitioners to design more effective and consumer-focused promotional strategies.